Cake Business Development through a SWOT Analysis Approach - Ahmad Firman; Fitriani Latief; Dirwan Dirwan (UNIVED Press, 2024)
This SWOT analysis can be used as a basis for business actors to achieve their business targets.This research aims to analyze and examine the development of the Al Fatih KItcken cake business.The research uses descriptive qualitative methods. The data sources in this research are:The primary data obtained was obtained from Al Fatih Kitchen through interviews, observation and documentation. The analysis method used is SWOT matrix analysis. The SWOT analysis method consists of combining the elements of strengths, weaknesses, opportunities and threats. The research results found that the SO strategy used by the medium-sized business Al Fatih Kitchen ismaintainquality and guaranteed production raw materials,medetermine the time and production plan in a well-scheduled manner; The ST strategy used by Al Fatih Kitchen ishave superior products as a characteristic of the business, Procurement of stock of raw materials needed to support the production process; The WO strategy used by Al Fatih Kitchen isPay attention to product attributesincludes taste, color, appearance, texture and aroma, mincreasethe entrepreneur's ability to carry out digital marketing and manage social media; The WT strategy used by Al Fatih Kitchen is to diversify the types of products offered and sold to consumers, carry out quality checking and control measures to ensure product quality.